Cross-cultural case study - Pole, Christopher J. (Christopher John), 1959-; Burgess, Robert G. (Amsterdam New York : JAI, 2000)
This volume is one of a series of research annuals on qualitative research designed to take up issues and debates in this area that relate to methodology, the relationship between data collection and data analysis, the relationship between theory and method, and the implications of qualitative research for social policy and evaluation.
Some Reflections on Cross-Cultural Interviewing / Jef C. Verhoeven -- Hecate's Domain: Ethnography at the Cultural Crossroads / Amanda Coffey, Paul Atkinson -- Some Issues and Problems in Cross-cultural Case Study Research / Robert G. Burgess -- Interviewing in a Cross-Cultural Context: Some Issues for Comparative Research / Patricia Broadfoot -- Deconstructing the Question: Reflections on Developing a Comparative Methodology for Research on Union Policy Towards Vocational Training / Estelle Krzeslo, Helen Rainbird, Catherine Vincent -- Internationalization and Doctoral Study: Some Reflections on Cross-Cultural Case Study Research / Ilse Beuselinck -- Case, Culture, Curriculum and Educational Change: Reflections on Cross-Cultural Case Study in England and Japan / Christopher J. Pole -- Educating Eaters: Cross-Cultural Approaches to Food and Eating in English and Danish Schools / Marlene Morrison, Jette Benn -- Qualitative Analysis: Phases, Techniques and Computer Use / Fred Wester, Vincent Peters -- Cross-Cultural Case Study Work. in Search of International Understanding in Educational Research / Michael Schratz.
Description based on print version record.
Keywords: Cross-cultural studies; Social sciences -- Methodology; Educational anthropology; Social research & statistics; Social Science -- Research